On quantum Markov chains on Cayley tree III: Ising model - Accardi, Luigi; Mukhamedov, Farrukh; Saburov, Mansoor (Springer, 2014)
In this paper, we consider the classical Ising model on the Cayley tree of order k (k ≥ 2), and show the existence of the phase transition in the following sense: there exists two quantum Markov states which are not quasi-equivalent. It turns out that the found critical temperature coincides with the classical critical temperature.